Pesantren Sosiopreneurs as Community Economic Development (Case Study at Integrated Islamic Boarding School of Al Mumtaz Gunungkidul Yogyakarta) - Muhammad Arif Kurniawan (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This research aimed to reveal in detail how the sociopreneur movement of Islamic Boarding School (Pondok Pesantren) Terpadu Al Mumtaz Gunungkidul Yogyakarta was used as a community economic development and to find out what were the strategies of Pesantren Al Mumtaz in driving its sociopreneur existence. This research was qualitative research with a case study approach. Data collection used observation, structured interviews, and documentation, while data analysis techniques used Miles and Huberman's model analysis. The research results showed that Pesantren Al Mumtaz had carried out the four stages of sociopreneurship well, including 1) the pesantren apprenticeship stage. 2) the pesantren launching stages. 3) the pesantren takeoff stage. 4) the pesantren maturity stages. Not only that, but this pesantren also had four strategies to promote its existence in the community, including: 1) collaborating with the local community by holding a Village Culinary Market regularly. 2) recruiting auxiliary staff from the community for various pesantren productions. 3) cooperating with the Regional Government in providing community economic assistance. 4) renting community land to be used as productive land.